2015
DOI: 10.3748/wjg.v21.i8.2387
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of scoring systems in predicting the severity of acute pancreatitis

Abstract: Various scoring systems showed similar predictive accuracy for severity of AP. Unique models are needed in order to achieve further improvement of prognostic accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
140
6
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(182 citation statements)
references
References 35 publications
13
140
6
12
Order By: Relevance
“…It includes Ranson's criteria, the Acute Physiology And Chronic Health Evaluation (APACHE II) score, Bedside Index for Severity in Acute Pancreatitis (BISAP), Computed Tomography Severity Index (CTSI), etc. [3][4][5] Knaus et al proposed a scoring system APACHE in 1981 taking into consideration of 34 possible measurements obtained during the first day of admission to ICU. 6 In 1985 Knaus et al developed APACHE II scoring system incorporating age and chronic health problems to physiological and laboratory values.…”
mentioning
confidence: 99%
“…It includes Ranson's criteria, the Acute Physiology And Chronic Health Evaluation (APACHE II) score, Bedside Index for Severity in Acute Pancreatitis (BISAP), Computed Tomography Severity Index (CTSI), etc. [3][4][5] Knaus et al proposed a scoring system APACHE in 1981 taking into consideration of 34 possible measurements obtained during the first day of admission to ICU. 6 In 1985 Knaus et al developed APACHE II scoring system incorporating age and chronic health problems to physiological and laboratory values.…”
mentioning
confidence: 99%
“…Patients with CB − had worse outcomes in terms of needing more ICU care but median length of stay for both groups was not statistically significant (P=0.15). SIRS, & BISAP scores and Balthazar CT severity index have been shown to be reliable indicators in predicting severity of pancreatitis (38)(39)(40)(41)(42) and have comparable efficacy in predicting the severity of AP (43,44). We also used the BUN level as a marker of disease severity in our study, as BUN has been shown to be a marker of persistent organ failure in AP (14) and any BUN above 20 mg/dL and any rise in BUN have been associated with mortality (15,45).…”
Section: Discussionmentioning
confidence: 99%
“…15 Different modalities are available for predicting aetiology, severity and outcome of acute pancreatitis with different sensitivity and specificity. Moreover some are not widely available, some are very expensive.…”
Section: Discussionmentioning
confidence: 99%